1985
DOI: 10.1104/pp.77.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Light and Temperature Regulation of Early Morning Crassulacean Acid Metabolism in Opuntia erinacea var Columbiana (Griffiths) L. Benson

Abstract: During the early morning period, light and temperature exert distinctively different influences on the gas exchange patterns of the Crassulacean acid metabolism plant Opuntia erinacea through their effects on acid metabolism. An initial decrease in CO2 uptake was triggered by illumination and was apparently due to a decreased CO2 diffusion gradient through light-mediated decarboxylation of malate. In contrast, the morning burst of CO2 uptake occurred at high temperature presumably in response to increases in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Light is essential for plant growth, with both wavelength and intensity affecting plant growth and morphogenesis (Yanagi et al, 2006;Mortensen and Stromme, 1987). Studies have shown that light intensity affects the elongation of the cactus stem and the malate content of cladodes (North et al, 1995;Littlejohn et al, 1985). However, to our knowledge, few studies have investigated the relationship between the light environment and growth of edible cacti (North et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Light is essential for plant growth, with both wavelength and intensity affecting plant growth and morphogenesis (Yanagi et al, 2006;Mortensen and Stromme, 1987). Studies have shown that light intensity affects the elongation of the cactus stem and the malate content of cladodes (North et al, 1995;Littlejohn et al, 1985). However, to our knowledge, few studies have investigated the relationship between the light environment and growth of edible cacti (North et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroponics is used as a basic cultivation system in plant factories, which are horticulture greenhouses or automated facilities where vegetables and other crops can be produced throughout the year by controlling the environmental conditions, such as light, temperature, humidity, CO2, and nutrient availability (Hirama 2015;Yanata & Takata 2014). Light is essential for plants, with both the wavelength and intensity affecting plant growth and morphogenesis (Mortensen & Strømme 1987;Yanagi et al 2006), and previous studies have shown that light intensity affects the elongation growth of the stems and the malate content of the cladodes in cacti (Littlejohn & Ku 1985;North et al 1995). However, few studies have investigated the relationship between the light environment and cladode growth in edible cacti, an understanding of which is important for improving the production and quality of these crops.…”
Section: Introductionmentioning
confidence: 99%